Antimicrobial Resistance Profile of Zoonotic Clinically Relevant WHO Priority Pathogens - Elaine Meade; Mark Anthony Slattery; Mary Garvey (Pathogens)
The World Health Organization announced critically important bacterial and fungal pathogens displaying alarming levels of antimicrobial resistance, which currently represent difficult-to-treat cases of morbidity. Within this grouping, the ESKAPE pathogens (Enterococcus faecium, Staphylococcus aureus, Klebsiella pneumoniae, Acinetobacter baumannii, Pseudomonas aeruginosa, and Enterobacter species) are causative of significant morbidity and mortality. Studies described herein demonstrate the presence of critically important fungal and ESKAPE bacterial species in companion animals which are zoonotic in nature. The relationship between the environment, animals, and human infectious disease has long been recognized as part of One Health. This research investigates the resistance patterns of isolated zoonotic pathogens using recognized in vitro methodologies, namely disk diffusion, minimum inhibitory concentration testing, and genetic screening. Antibiotic susceptibility testing and gene analysis demonstrated an association between multi-drug resistance and extended beta spectrum lactamase production in critical-priority bacteria. Escherichia coli, Klebsiella pneumoniae, Acinetobacter baumannii, and Pseudomonas aeruginosa exhibit great levels of multi-drug resistance. Fungal isolates demonstrated high levels of resistance, with Amphotericin B proving the most effective antifungal agent investigated. The level of antimicrobial resistance present in clinically relevant bacterial and fungal pathogens isolated from animal cases of morbidity in this study is alarming. In conclusion, this study shows that animals can act as a reservoir facilitating the transmission of antibiotic-resistant pathogens and genes zoonotically.